1950
DOI: 10.1111/j.1467-6494.1950.tb01257.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Color on Reactions to Ink Blots*

Abstract: The Rorschach technique, despite its widespread clinical apphcation, has remained isolated from the mam body of theoretical and expenmental psychology The reasons for this isolation have been dearly analyzed by Thurstone (6) Among experimental psychologists it has been a commonplace to express the desirability of having the chniaan supply expenmental evidence to establish the saentific respectability of his techniques The experimentalists themselves have shown no eagerness to take over this task which they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1950
1950
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…Since publication of that article, a number of other experiments dealing with the influence of color have appeared, most of which have confirmed the original findings (1,2,3,4,6,7) Results which are at vanance with the study by Lazarus (5) have been reported by Supola et al (8,9) In one article by Siipola, Kuhns, and Taylor (9) a number of criticisms were offered of the Lazarus methodology and conclusions The purpose of the present article is to clarify some of the issues raised by Siipola's data and criticisms, to present reanalyzed data from the onginal study, and to discuss an additional expenment…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Since publication of that article, a number of other experiments dealing with the influence of color have appeared, most of which have confirmed the original findings (1,2,3,4,6,7) Results which are at vanance with the study by Lazarus (5) have been reported by Supola et al (8,9) In one article by Siipola, Kuhns, and Taylor (9) a number of criticisms were offered of the Lazarus methodology and conclusions The purpose of the present article is to clarify some of the issues raised by Siipola's data and criticisms, to present reanalyzed data from the onginal study, and to discuss an additional expenment…”
supporting
confidence: 70%
“…The present article has presented a reanalysis of data reported by Lazarus (5) concerning the influence of color on the Rorschach protocol This reanalysis was prompted by some criticisms by Siipola (8,9) Discrepancies between the findings of Lazarus and Siipola remain after the reanalysis and may be attributed in part to the use of usual details by Siipola and complete Rorschach mkblots by Lazarus An experiment is reported in which a senes of usual detail inkblots were colored m such a way that it was possible to compare the effects of congruous color-form combinations with incongruous colorform combinations, black with congruous, and black with incongruous combmations Only a few significant differences in response time and affective value were found as a function of these color manipulations, some of them reversing the predicted directions These effects were considered extremely small in magnitude when other factors such as the effect of blot structure and individual differences in response time are taken into account…”
Section: Discussionmentioning
confidence: 94%
“…The above results also suggest that there is a relationship between the amount of time a subject takes to respond and the degree to which he subsequently discriminates between different stimuli. Support for these findings and rationale is found in the studies of Siipola (1950) and Stein (1949). Siipola's study indicated that when the chromatic variable was added to the stimulus, the normal subject took more time to respond to it.…”
Section: Discussionmentioning
confidence: 83%
“…Still other investigators have measured different physiological functions of subjects while they were taking the Rorschach (Frost & Rodnick, 1948;Goodman, 1950;Levy, 1950). Another approach has been to extrapolate the color stimulus from the context of the Rorschach test to study response to color itself (Drechsler, 1960;Siipola, 1950). In general, the results of these studies were contradictory with the exception of the extrapolation method in which the findings were more positive.…”
Section: Michigan State Universitymentioning
confidence: 99%
“…Alternative inkblot instruments have been developed (Holtzman, 19581 Levy, 1948;Harrower, 19451 Zulliger-Behn, 1952), each accompanied by its o~m cache of research. Studies by Lazarus (1949) and Siipola (1950) have stimulated dramatic reconsiderations of the significance of color and color shock in Rorschach theory. Stimulus qualities of the blots have been given increasing attention OUtchell, 1952J George, 1955;Baughman, 1954Baughman, , 1965.…”
Section: The Inability Of Experimental Researchers To Demonstratementioning
confidence: 99%